Global Context of Industry 5.0 : Current Trends and Challenges in Indonesia - Rame Rame; Purwanto Purwanto; Sudarno Sudarno (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2023)
Industry 5.0, the latest advancement in production processes, emphasizes a collaborative and human-centered approach to manufacturing. This paradigm shift incorporates 3D printing, Augmented Reality (AR), Virtual Reality (VR), the Internet of Things (IoT), and Artificial Intelligence (AI) to potentially enhance environmental sustainability, process technology, and energy conservation. Although Industry 5.0 offers significant opportunities, its implementation in Indonesia faces several challenges, such as infrastructure development, human resource competency enhancement, and the establishment of supportive laws and regulations. Collaboration among government, industry, and academic institutions drives innovation and research. This review article examines the current state of Industry 5.0, the underlying technology, and the obstacles and opportunities in adopting this novel manufacturing approach. It highlights environmental impact, process technology, and energy conservation as critical areas for consideration. Indonesia can substantially improve these areas by leveraging the potential of Industry 5.0 and overcoming these challenges. The paper offers insights into Indonesia's integration of Industry 5.0 and explores the benefits this new paradigm can bring to the nation.